Clinical Ethics Support Services Are Not as Well-Established in Forensic Psychiatry as in General Psychiatry - Franke, Irina; Speiser, Oskar; Dudeck, Manuela; Streb, Judith (Frontiers in Psychiatry, 2020)
Background: Mental health care professionals deal with complex ethical dilemmas that involve the principles of autonomy, justice, beneficence, and non-maleficence. Such dilemmas are even more prominent in forensic mental health care, where the restriction of personal rights is legitimated not only by patient well-being but also by public safety interests. Little is known about either the use of formal ethics support services or specific ethical needs in forensic mental health care. Knowledge about the current structures and how they compare with those in general psychiatry would help to identify the most important ethical issues and to analyze whether there are unmet needs that might require specific ethics support. Methods: We performed a survey study in all general psychiatric and forensic psychiatric inpatient departments in Germany. The aims were to compare the availability and functioning of clinical ethics structures and to identify specific ethical needs in inpatient forensic and general mental health care. Results: Clinical ethics support was available in 74% of general psychiatric hospitals but in only 43% of all forensic psychiatric hospitals and 25% of those offering treatment for offenders with substance use disorders. Most ethics support services were interdisciplinary. The most frequently requested retrospective and prospective ethics consultations were on issues of omission and termination of treatment, coercive measures, and advance directives. Among the hospitals without access to ethics support, 71% indicated a need for training in ethics. Discussion: Our results show that ethics consultation is well established in general psychiatry, but less so in forensic psychiatry. Mental health care professionals in forensic psychiatry seem to have a need for ethics support and training in clinical ethics. We also found a difference in access to ethics structures between hospitals that treat mentally disordered offenders and those that treat offenders with substance use disorders. Further research should focus on how ethics support can be comprehensively implemented in forensic mental health care and how this might improve treatment quality and patient and staff well-being.